Evidence of Infection in Humans with Rickettsia helvetica in Eastern France - Pierre-Edouard Fournier (Emerging Infectious Diseases, 2000)
A 37-year-old man living in eastern France seroconverted to Rickettsia helvetica in August 1997, 4 weeks after the onset of an unexplained febrile illness. Results of a serosurvey of forest workers from the area where the patient lived showed a 9.2% seroprevalence against R. helvetica. This organism may pose a threat for populations exposed to Ixodes ricinus ticks.